Description of Bullying Incidents in Students at Public School 02 Mereng - Maulida Hasanah; Noor Yunida Triana; Murniati Murniati (Universitas Ibn Khaldun Bogor, 2023)
The incidence of bullying in elementary school students has become a trend today. The Indonesian Child Protection Commission (KPAI) provided data related to bullying incidents from January to April 2019, there were 25 reported cases of bullying, covering about 67% of all cases reported at the primary/equivalent education level. The purpose of this study was to determine the picture of bullying incidents that often occur at SDN 02 Mereng. This study used quantitative descriptive analysis methodology, with a cross-sectional design through the form of a survey, the instrument in this study used a questionnaire that had been tested for validity with a calculated r-value of >0.325 and a reliability test with a Cronbach's Alpha value of 0.786. Data were tested by univariate analysis. It was found that the majority of respondents were female (64%/), the majority aged 12 years (40.5%), and the incidence of bullying in the High category (58.8%). This shows that bullying incidents at SDN 02 Mereng still occur a lot. The form of bullying that often occurs is physical bullying, although there is also verbal bullying.